Can neurofeedback training enhance performance? An evaluation of the evidence with implications for future research - Vernon, D. J. (Applied Psychophysiology and Biofeedback, 2005)
There have been many claims regarding the possibilities of performance enhancement training. The aim of such training is for an individual to complete a specific function or task with fewer errors and greater efficiency, resulting in a more positive outcome. The present review examined evidence from neurofeedback training studies to enhance performance in a particular area. Previous research has documented associations between specific cortical states and optimum levels of performance in a range of tasks. This information provides a plausible rationale for the use of neurofeedback to train individuals to enhance their performance. An examination of the literature revealed that neurofeedback training has been utilised to enhance performance from three main areas; sport, cognitive and artistic performance. The review examined evidence from neurofeedback training studies within each of these three areas. Some suggestive findings have been reported with regard to the use of neurofeedback training to enhance performance. However, due to a range of methodological limitations and a general failure to elicit unambiguous changes in baseline EEG activity, a clear association between neurofeedback training and enhanced performance has yet to be established. Throughout, the review highlights a number of recommendations to aid and stimulate future research.